2017
DOI: 10.1097/gme.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal symptom clusters and their correlates in women with and without a history of breast cancer: a pooled data analysis from the Women's Wellness Research Program

Abstract: In this study, women after treatment for breast cancer reported a broad range of bothersome climacteric symptoms. Similar symptom clusters were also noted for women with and without a history of breast cancer, though correlates differed across groups, and might reflect different underlying etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 50 publications
5
45
0
Order By: Relevance
“…In the current study, the number of comorbidities was reported as a significant predictor of symptom clusters (class 2 and class 4), characterized by a moderate level of pain. The finding of greater risk for higher symptom burden in cancer survivors with comorbid conditions is consistent with previous studies (Roiland & Heidrich, 2011;Seib et al, 2017;Shi et al, 2011). Seib et al (2017) showed that peripheral somatic symptoms were higher among breast cancer survivors who reported comorbidities.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the current study, the number of comorbidities was reported as a significant predictor of symptom clusters (class 2 and class 4), characterized by a moderate level of pain. The finding of greater risk for higher symptom burden in cancer survivors with comorbid conditions is consistent with previous studies (Roiland & Heidrich, 2011;Seib et al, 2017;Shi et al, 2011). Seib et al (2017) showed that peripheral somatic symptoms were higher among breast cancer survivors who reported comorbidities.…”
Section: Discussionsupporting
confidence: 91%
“…The finding of greater risk for higher symptom burden in cancer survivors with comorbid conditions is consistent with previous studies (Roiland & Heidrich, 2011;Seib et al, 2017;Shi et al, 2011). Seib et al (2017) showed that peripheral somatic symptoms were higher among breast cancer survivors who reported comorbidities. Another study in cancer survivors found that the likelihood of high symptom burden increased with the number of comorbidities (Shi et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations